LEGAL ANALYSIS OF LEGAL PROTECTION OF CHILDREN FROM ECONOMIC EXPLOITATION AND VIOLENCE IN INDONESIA STUDY IN MEDAN CITY - Ismaidar, Ismaidar; Sumarno, Sumarno; Harun Firman Kurniansyah (International Journal of Synergy in Law, Criminal, and Justice, 2024)
This study analyzes the legal effectiveness of the implementation of Law No. 35 of 2014 concerning Child Protection in overcoming economic exploitation and violence against children in Medan City. Economic exploitation of children and violence are still serious problems that require effective legal intervention. Through a mix method approach, this study evaluates the role of social institutions and law enforcement officers in handling cases of child exploitation, with a focus on challenges in the implementation of child protection policies. The results of the study indicate that although child protection regulations already exist, their effectiveness is still hampered by weak supervision, minimal resources, and low awareness of the community and law enforcement officers. Weak coordination between social institutions and law enforcement is also a major obstacle. This study recommends increasing the capacity of law enforcement officers, strengthening proactive social programs, and revising policies to ensure more optimal protection for children in Medan City. Close cooperation is needed between the government, community, and law enforcement to minimize economic exploitation of children and violence in a wider scope.